Conceptual programming in GIS development - Ya Tsvetkov, V; Buravtsev, A V (IOP conference series. Earth and environmental science, 2021)
The article explores the application of conceptual programming methods in the development of software for geographic information systems. The connection between conceptual and functional programming through the apparatus of functional grammars is shown. It is proved that a natural language in conceptual programming can be expressed through a domain-specific language, which is an integral part of language-oriented programming. The article proposes the implementation of conceptual programming ideas by combining functional and language-oriented programming styles. It is proved that this approach is more acceptable in comparison with the imperative approach for conceptualizing the subject area. Approach implementation example for a geographic information system for maintaining an address register is given. The example uses the multi-paradigm functional programming language F#. The article proposes a new approach to constructing algorithms called constructive algorithms. It is based on the principles of conceptual design and conceptual programming. This approach improves the quality and speed of geographic information systems development through the use of ontological algorithms.